Identifikasi Kebutuhan Siswa Penyandang Disabilitas Pasca Sekolah Menengah Atas - Rizky, Ulfah Fatmala (Indonesian Journal of Disability Studies, 2014)
The reseach aims to identify necessities of students with disability post-Senior High School, either in inclusive school or special school. The purpose of this research is to describe the necessities of student with disability post-Senior High School. Therefore, students's planning post-Senior High School will be the priority in this research. The reseach used a qualitative method. The focuses of this research are, first, history of Special School. Second, the sight of special schol towards inclusive education. Third, identification of ideal school for students with disability. Fourth, identification of students's planning post-Senior Hgh School. The locations of this research are, first, SLB Negeri Semarang (Public Special School of Semarang). Second, SLB YPTB Malang (YPTB Special School), Third, Universitas Brawijaya (Brawijaya University). The method of collecting data in this research uses observation, interview, and documentation. The conclusions obtained from this research are, first, both of special school in this research have not special program to equip the students post-Senior High School. Second, 67,85% of students with disability planned to seek ajob post-Senior High School. Third, 42,85% of students with disability estimate themselves having the opportunity to carry on their education in University, but that is not their priority.